A rare but very serious disease: Tumors metastasizing to the thyroid in the light of cases - Balta, Hilal; Kocaman, Nevin; Ucer, Ozlem (Elsevier Ltd, 2022)
Introduction: Metastasis to the thyroid gland is a rare condition that can pose diagnostic difficulties. The purpose of the present study was to provide an overview of non-thyroid tumors metastasizing to the thyroid based on our institutional experience. Material and method: The data of the study were obtained by using the pathology database investigating patients diagnosed with tumor metastasis to° the thyroid between 2013 and 2022 at Firat University Hospital and reviewing their medical files. Results: As a result of histochemical and immunohistochemical examinations of the thyroid, seven patients were diagnosed with tumor metastasis. Of the seven patients, 3 (42.85%) were female and 4 (57.14%) were male. The median age at which thyroid metastases were detected was 60.71 (52?80). The most common metastatic thyroid tumors of primary origin were kidney (28.5%), lung (28.5%), head and neck malignancies (28.5%) and unknown primary tumors (14.5%). The median time from diagnosis of primary tumor to diagnosis of thyroid metastasis was 26 months (12?36). The longest survival was determined in clear cell renal cell carcinoma, and the shortest survival was determined in lung cancer. Conclusion: Thyroidal metastases are rare; however, they must be suspected in patients with a previous history of non-thyroid malignancy and a thyroid nodule. The prognosis is quite poor and the overall survival of the patient depends on the type and location of the primary tumor. The most common primary tumors metastasizing to the thyroid are kidney, lung, and head and neck malignancies, and surgery/chemotherapy may be beneficial. © 2022 Elsevier Ltd
Keywords: Carcinoma; Metastasis; Thyroid; Tumor-to-tumor metastasis